Reduction on Propositional Logic Set based on Correlation Analysis - Zhi Huilai (Institute of Advanced Engineering and Science, 2014)
A knowledge base is redundant if it contains parts that can be inferred from the rest of it. In this paper, with no district bound, we study the reduction theory and algorithm on proposition logic set. The propositions of a given proposition set fall into three categories: necessary proposition, useful proposition, and useless proposition. A reduction of a given set is composed of all the necessary propositions and some useful propositions. At the beginning we introduce induced formal context of proposition set, and then propose the method of reduction on proposition set based on correlation analysis.